Farmers nutrient management practices in indigenous cropping systems in southern Cameroon - Buttner, U.; Hauser, S. (Elsevier, 2003)
With increasing population densities, food production needs to be increased. A common response of farmers is to shorten fallow periods, which can lead to a decline in crop yields, due to incomplete nutrient replenishment. However, whether farmers change their management of soil and nutrients according to the fallow length is not known. A survey was carried out in southern Cameroon in 1995 to establish factors determining farmers’ nutrient management practices (NMPs). Three classes of indigenous NMPs were identified: crop placement, mulching, and the use of inputs. Crop placement comprised intentional cultivation of certain crops in ash patches or near to tree trunks and stumps. Mulching was done with weeds and crop residues, on the soil surface next to crops or in planting holes. Crop placement was found in 88.8% of fields and mulching in 57.4%, while inputs were used in only 1.7%. Nutrient management seemed to be restricted to an optimal allocation of crops to nutrient sources in the field. Relationships were weak between the frequency of crop placement or mulching and indices of land or labor availability. Fallow length seems to be negatively correlated to crop placement at rotten trunks or stumps or in ash patches and positively to placement near recently felled trees. Crop placement and mulching of crop residues were used less often in simplified crop associations than in traditional intercrops. Nutrient inputs were mainly given to monocrops. Application of purchased inputs concentrated on commercial crops. Most respondents knew the advantages and risks of currently practiced methods, but often lacked information on the use of locally available internal inputs (refuse, kitchen ash, manure). Application of internal inputs was considered too labor demanding. The use of purchased inputs was limited by high prices. Soil fertility was in most cases not regarded as a problem.